Ketone body therapy: from the ketogenic diet to the oral administration of ketone ester - Hashim, Sami A. (J Lipid Res, 2014)
Ketone bodies (KBs), acetoacetate and β-hydroxybutyrate (βHB), were considered harmful metabolic by-products when discovered in the mid-19th century in the urine of patients with diabetic ketoacidosis. It took physicians many years to realize that KBs are normal metabolites synthesized by the liver and exported into the systemic circulation to serve as an energy source for most extrahepatic tissues. Studies have shown that the brain (which normally uses glucose for energy) can readily utilize KBs as an alternative fuel. Even when there is diminished glucose utilization in cognition-critical brain areas, as may occur early in Alzheimer’s disease (AD), there is preliminary evidence that these same areas remain capable of metabolizing KBs. Because the ketogenic diet (KD) is difficult to prepare and follow, and effectiveness of KB treatment in certain patients may be enhanced by raising plasma KB levels to ≥2 mM, KB esters, such as 1,3-butanediol monoester of βHB and glyceryl-tris-3-hydroxybutyrate, have been devised. When administered orally in controlled dosages, these esters can produce plasma KB levels comparable to those achieved by the most rigorous KD, thus providing a safe, convenient, and versatile new approach to the study and potential treatment of a variety of diseases, including epilepsy, AD, and Parkinson’s disease.